Faktor – Faktor yang Berhubungan dengan Penerapan Higiene Sanitasi pada Kantin Sekolah Dasar di Kota Sungai Penuh Tahun 2022 - Hafiz Nuzil Akbar; Usi Lanita; Fajrina Hidayati (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2023)
Sanitary hygiene is a condition and preventive measure needed to ensure food safety before processing until it is served consumption. The purpose of this study was to determine the factors related to the implementation of primary school canteen sanitation hygiene in the scope of the city of Sungai Penuh 2022. Quantitative method using a cross-sectional approach. The population is all food handlers in the Elementary School canteen in full river city scope. The sample is 100 respondents from 69 elementary schools, the sample technique uses purposive sampling. Bivariate analysis using the chi-square test, the relationship between the independent variable and the dependent variable is the relationship between knowledge (p=0.000), participation in training (p=0.027), supervision (p=0.000), and availability of sanitation facilities (p=0.000). with the implementation of elementary school canteen sanitation hygiene. Meanwhile, the attitude variable (p=0.594) had nothing to do with the implementation of school canteen hygiene and sanitation. There is a relationship between knowledge, participation in training, supervision, and the availability of sanitation facilities with the implementation of elementary school canteen sanitation hygiene in the 2022 full river city scope, and there is no relationship between attitude and the implementation of elementary school canteen sanitation hygiene in the 2022 full river city scope (p= 0.594). It is hoped that the Sungai Penuh City Health Office and the Puskesmas in the sub-district work area will improve supervision and routinely carry out canteen sanitation hygiene training and counseling, and food handlers are expected to be available to attend and provide sanitation facilities at their place of business.